Taking it to the bank: the ethical management of individual findings arising in secondary research - Graham, M; Hallowell, N; Solberg, B; Haukkala, A; Holliday, J; Kerasidou, A; Littlejohns, T; Ormondroyd, E; Skolbekken, J-A; Vornanen, M (BMJ Publishing Group, 2021)
A rapidly growing proportion of health research uses ‘secondary data’: data used for purposes other than those for which it was originally collected. Do researchers using secondary data have an obligation to disclose individual research findings to participants? While the importance of this question has been duly recognised in the context of primary research (ie, where data are collected from participants directly), it remains largely unexamined in the context of research using secondary data. In this paper, we critically examine the arguments for a moral obligation to disclose individual research findings in the context of primary research, to determine if they can be applied to secondary research. We conclude that they cannot. We then propose that the nature of the relationship between researchers and participants is what gives rise to particular moral obligations, including the obligation to disclose individual results. We argue that the relationship between researchers and participants in secondary research does not generate an obligation to disclose. However, we also argue that the biobanks or data archives which collect and provide access to secondary data may have such an obligation, depending on the nature of the relationship they establish with participants.